الضغوط المهنية و علاقتها بالمسار الوظيفي دراسة ميدانية على عينة من عمال مؤسسة سونلغاز بولاية الأغواط - بن بوزيد سفيان; تقاري عبد القادر; علي قويدري (My University, 2023)
this study aimed to reneal relationship between occupational pressures and the career path in a sample of sonelgaz workers data collection was processed by the statistical package for social sciences spss version (22) where the following result were reached : - there is a statistically significant relationship between exceptional pressure and career path in a sample of sonelgaz workers - there are no statistically significant differences in the level of occupational pressure according to the gender variable (male, female) - there are statistically significant differences in the level of occupational pressure according to the professional experience variable (less than 10 years and more than 10 years) - keywords: occupational pressures -career path